2015
DOI: 10.1186/s13643-015-0114-3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for preventing or treating malnutrition in problem drinkers who are homeless or vulnerably housed: protocol for a systematic review

Abstract: BackgroundProblem alcohol drinking in homeless and vulnerably housed people can lead to malnutrition, which is associated with complications such as alcohol-related brain damage. Homeless alcohol drinkers are likely to have worse health outcomes and different nutritional needs compared with housed alcohol-drinking persons. It is not clear whether interventions to improve nutritional status in this population have been effective. The purpose of this review is to assess the effectiveness and cost-effectiveness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
1
10
0
1
Order By: Relevance
“…Encouraging older adults without diseases to quit smoking has the potential to reduce the risk of the development of diseases and improve quality of life, besides to emphasizing the adoption of a healthy lifestyle as an important strategy in the relationship between smoking and BMI. The relationship between underweight/ malnutrition and alcohol abuse is described in the literature 23 . It is estimated that alcohol abuse contributed to 5.9% of deaths worldwide in 2012, which occurred mainly due to heart disease and diabetes (33.4%), gastrointestinal disease (16.2%) and malignant tumors in various sites (12.5%) 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Encouraging older adults without diseases to quit smoking has the potential to reduce the risk of the development of diseases and improve quality of life, besides to emphasizing the adoption of a healthy lifestyle as an important strategy in the relationship between smoking and BMI. The relationship between underweight/ malnutrition and alcohol abuse is described in the literature 23 . It is estimated that alcohol abuse contributed to 5.9% of deaths worldwide in 2012, which occurred mainly due to heart disease and diabetes (33.4%), gastrointestinal disease (16.2%) and malignant tumors in various sites (12.5%) 24 .…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in the city of Campinas, Brazil, reports a similar finding, as alcohol use once a week was associated with aspects of happiness and a good assessment of one's health status 27 . However, there is ample evidence that alcohol use, particularly binge drinking, increases the risk of accidents and violence 28 and has harmful consequences for the gastrointestinal system, such as gastritis, diarrhea and poor nutrient absorption 23 , which can further aggravate weight loss/malnutrition in older adults. It should be stressed that the study only identified surviving individuals and their current level of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Problem-drinking is a commonly used term with no agreed definition. We therefore included all definitions of problem-drinking, as defined by included study authors [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…References of included studies were screened and authors were contacted to find any additional studies or data. The search was published in the protocol [ 28 ] and is up to date until 16th November 2016.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation